Decision-Making Process and Reasoning of Laparoscopic Entry: A Questionnaire-Based Analysis of Surgical Practice: A Cross-Sectional Study - Şişik, Abdullah; Başak, Fatih; Hasbahçeci, Mustafa; Köse, Emin; Kudaş, İlyas and Okan, İsmail (Cerrahpaşa Medical Journal, 2021)
Objective: Several techniques for initial abdominal entry in laparoscopy have been introduced in the literature. Various guidelines and recommendations are available on this subject; however, compliance with these findings is controversial. The purpose of this study is to evaluate the rationale and the process of decision-making for the first entry technique in laparoscopy. Methods: A close-ended survey question was formed. The survey was sent to general surgeons by e-mail with the survey's web address included and administered face-to-face in the National Congress of General Surgery. Descriptive statistical methods (mean, standard deviation, median, frequency, ratio, minimum, and maximum) were used to evaluate the study data. Relevance was calculated as P < .05 in the 95% CI. Results: A total of 263 surveys were evaluated. The most common preferred method was the "Veress needle technique" during the residency of the participants. However, fewer surgeons preferred this method (P < .001), the open approach/Hasson trocar (P = .004) and direct trocar insertion (P = .003) were more prevalent after residency. The most common rationale for choosing the laparoscopic entry technique was "learned laparoscopic entry technique during residency" (38.0%) and "ease of applicability" (27.0%). Reasons for changing the laparoscopic entry technique during surgical practice are "easy applicability" in 37% and "advice of competent people on general surgery" in 24.4% of participants. Conclusion: This study revealed that the decision-making for initial abdominal entry for laparoscopy was influenced mainly by the surgeon's experience during residency, the mentors' effect, and ease of applicability of a technique. Laparoskopik Girişin Karar Verme Süreci ve Gerekçelendirilmesi: Cerrahi Pratiğin Anket Temelli Analizi: Kesitsel Bir Çalışma Amaç: Literatürde laparoskopik ameliyatlarda ilk trocar girişi için birkaç teknik tanıtılmıştır. Bu konuda çeşitli kılavuzlar ve öneriler mevcuttur, ancak bunlara uyulması tartışmalıdır. Bu çalışmanın amacı, laparoskopide ilk trocar giriş tekniğinin gerekçesini ve karar verme sürecini değerlendirmektir. Yöntemler: Katılımcılar için kapalı uçlu anket soruları oluşturuldu. Anket, anketin web adresi ile birlikte e posta yoluyla genel cerrahlara gönderildi ve ayrıca Ulusal Cerrahi Kongresi'nde yüz yüze uygulandı. Çalışma verilerini değerlendirmek için tanımlayıcı istatistiksel yöntemler (ortalama, standart sapma, medyan, frekans, oran, minimum ve maksimum) kullanıldı. Anlamlılık %95 güven aralığında P < ,05 olarak hesaplandı. Bulgular: Toplam 263 anket değerlendirildi. Katılımcıların asistanlığı sırasında en çok tercih edilen yöntem “Veress iğne tekniği” olarak saptandı. Ancak asistanlık sonrasında bu yöntemin daha az tercih edildiği (P < ,001), açık yaklaşım / Hasson trokar (P = ,004) ve direkt trokar yerleştirme (P = ,003) yöntemlerinin daha popular olduğu saptandı. Laparoskopik giriş tekniğinin tercih edilmesinin en yaygın gerekçesi “ihtisas döneminde öğrenilmiş laparoskopik giriş tekniği” (%38,0) ve “uygulanabilirlik kolaylığı” (%27,0) idi. Cerrahi uygulama sırasında laparoskopik giriş tekniğini değiştirme nedenleri %37'sinde “kolay uygulanabilirlik” ve %24,4'ünde “genel cerrahi konusunda yetkin kişilerin tavsiyesi” olarak bulundu. Sonuç: Bu çalışma, bir cerrahın laparoskopi için ilk karın girişine karar vermesinin, çoğunlukla uzmanlık süresindeki deneyimi, mentorların etkisi ve bir tekniğin uygulanabilirlik kolaylığından etkilendiğini ortaya koydu. Cite this article as: Şişik A, Başak F, Hasbahçeci M, Köse E, Kudaş İ, Okan I. Decision process and reasoning of laparoscopic entry: A questionnaire-based analysis of surgical practice: A cross-sectional study. Cerrahpaşa Med J. September 27, 2021. 46(1):6-11.